Treating Dyslipidemia for the Primary and Secondary Prevention of Stroke - Barkas, Fotios; Milionis, Haralampos (Seminars in Neurology, 2017)
Stroke is associated with a heavy burden of mortality and disability, underscoring the importance of effective primary and secondary prevention measures. Dyslipidemia as a risk factor for ischemic stroke has long been disputed. Nevertheless, accumulating epidemiological evidence supports a role of lipid abnormalities in increasing ischemic stroke risk and representing a potential target for therapeutic interventions. 3-hydroxy-3-methyl-glutaryl- (HMG-) CoA reductase inhibitors (i.e., statins) are currently the mainstay of therapy for the management of hypercholesterolemia in patients with cardiovascular disease and stroke. Although their beneficial effects on stroke risk have been attributed chiefly to their lipid-lowering capacity, they also have pleiotropic effects. Other lipid lowering modalities have been shown to reduce the risk of ischemic stroke in individuals at high cardiovascular risk, but data regarding their use in secondary stroke prevention are lacking.
Keywords: dyslipidemia; ischemic stroke; lipid-lowering treatment; prevention; statin